2018
DOI: 10.18488/journal.aefr.2018.810.1211.1225
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Luxury Housing on Neighborhood Housing Prices in Taipei City

Abstract: This study investigated whether a decision to construct luxury housing can help increase neighborhood housing prices. The difference-in-difference method was used in the analysis. Housing transaction data from 2008 to 2011 were used in the analysis. According to the empirical results, after eliminating the common growth in prices (10.6%) between the neighborhood in which luxury housing was to be built and the other non-luxury neighborhood, the real gap in the housing prices caused by the luxury housing was 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…In addition to the external effects of housing, Hsu (2005) suggested that individual housing needs can also increase the BIRG phenomenon due to surrounding community characteristics; this involves location-, brand-, and quality-related cognition dimensions, all of which produce the neighborhood effect of luxury housing. The results corresponded to those reported by Ooi and Le (2013), François et al (2002), Tang and Yao (2012), and Lee et al (2018), that is, new constructions in neighboring areas are attractive and produce a positive effect. For example, the Olympics increased housing prices in Beijing that were particularly high in the periods close to the opening of the Olympics.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In addition to the external effects of housing, Hsu (2005) suggested that individual housing needs can also increase the BIRG phenomenon due to surrounding community characteristics; this involves location-, brand-, and quality-related cognition dimensions, all of which produce the neighborhood effect of luxury housing. The results corresponded to those reported by Ooi and Le (2013), François et al (2002), Tang and Yao (2012), and Lee et al (2018), that is, new constructions in neighboring areas are attractive and produce a positive effect. For example, the Olympics increased housing prices in Beijing that were particularly high in the periods close to the opening of the Olympics.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed that factors relating to the Olympics resulted in a progressive increase and subsequent decrease of neighboring real estate prices, whereas in cities outside the influence of the Olympics, real estate prices changed in line with the economic cycle. Lee et al (2018) examined the difference in housing prices within and outside the areas neighboring luxury housing. The experimental group included an area within 500 meters of luxury housing and the control group included areas outside this range.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations